2016
DOI: 10.1142/s0218195916500059
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bounds on the Dilation of Plane Spanners

Abstract: Abstract(I) We exhibit a set of 23 points in the plane that has dilation at least 1.4308, improving the previous best lower bound of 1.4161 for the worst-case dilation of plane spanners.(II) For every n ≥ 13, there exists an n-element point set S such that the degree 3 dilation of S equals 1 + √ 3 = 2.7321 . . . in the domain of plane geometric spanners. In the same domain, we show that for every n ≥ 6, there exists a an n-element point set S such that the degree 4 dilation of S equals 1 + (5 − √ 5)/2 = 2.1755… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…In the geometric setting, where the vertices are embedded in a metric space, spanners have been studied in [3,10,12,13,26,28] and many other papers. In particular, plane geometric spanners were studied in [7,8,17,16]. The reader is also referred to the surveys [8,20,30] and the monograph [33] dedicated to this subject.…”
Section: :3mentioning
confidence: 99%
“…In the geometric setting, where the vertices are embedded in a metric space, spanners have been studied in [3,10,12,13,26,28] and many other papers. In particular, plane geometric spanners were studied in [7,8,17,16]. The reader is also referred to the surveys [8,20,30] and the monograph [33] dedicated to this subject.…”
Section: :3mentioning
confidence: 99%
“…In the geometric setting, where the vertices are embedded in a metric space, spanners have been studied in [3,8,10,11,22,24] and many other papers. In particular, plane geometric spanners were studied in [5,6,14,15]. The reader is also referred to the surveys [6,17,25] and the monograph [27] dedicated to this subject.…”
Section: Related Work Peleg and Schäfermentioning
confidence: 99%
“…In two special cases, Bose et al [5] showed that reducing the degree to 3 is possible. In terms of lower bounds, Dumitrescu and Ghosh [19] showed that there exist point sets that require a spanning ratio of at least 1.4308. They also strengthened this bound to 2.1755 for spanners of degree 4 and 2.7321 for spanners of degree 3.…”
Section: Introductionmentioning
confidence: 99%